Analysis of extraction level performance at the Henderson Mine - Sainsbury, DP; Loring, DM (Ground Support 2013: Seventh International Symposium on Ground Support in Mining and Underground Construction, 2013)
The 7210 Level at Henderson Mine in Colorado, USA commenced production in January 2005. However, after undercutting commenced, unusual damage was noted on the western side of the drawpoint brows and entry ribs. A convergence monitoring system was developed to measure the convergence in the drawpoints as a tool to manage damage throughout the extraction level. Vertical convergence readings confirmed that substantial deformations (>5% strain) were occurring and modifications were made the drawpoint construction methodology in an attempt to limit the damage. A numerical analysis of the observed and monitored extraction level performance during the early stages of the 7210 Level has been conducted. A close match between the measured and modelled vertical convergence at multiple locations throughout the extraction level was obtained. The numerical simulation results were used to verify the modes of damage within the drawpoints and predict the performance of the modified drawpoint construction methodology over the remainder of the panel.